A method for analyzing programmed cell death in xylem development by flow cytometry - Liu, Ying-Li; Guo, Ying-Hua; Song, Xue-Qin; Hu, Meng-Xuan; Zhao, Shu-Tang (Frontiers in Plant Science, 2023)
Programmed cell death (PCD) is a genetically regulated developmental process leading to the death of specific types of plant cells, which plays important roles in plant development and growth, such as wood formation. However, an efficient method needs to be established to study PCD in woody plants. Flow cytometry is widely utilized to evaluate apoptosis in mammalian, while it is rarely used to detect PCD in plants, especially in woody plants. Here, we reported that the xylem cell protoplasts from poplar stem were stained with a combination of fluorescein annexin V-FITC and propidium iodide (PI) and then sorted by flow cytometry. As expected, living cells (annexin V-FITC negative/ PI negative), early PCD cells (annexin V-FITC positive/ PI negative), and late PCD cells (annexin V-FITC positive/ PI positive) could be finely distinguished through this method, and then subjected for quantitative analysis. The expression of cell-type and developmental stages-specific marker genes were in consistent with the cell morphological observation. Therefore, the newly developed fluorescence-activated cell sorting (FACS) method can be used to study PCD in woody plants, which will be beneficial for studying the molecular mechanisms of wood formation.